2017
DOI: 10.1038/srep42651
|View full text |Cite
|
Sign up to set email alerts
|

The Biophysical Probes 2-fluorohistidine and 4-fluorohistidine: Spectroscopic Signatures and Molecular Properties

Abstract: Fluorinated amino acids serve as valuable biological probes, by reporting on local protein structure and dynamics through 19F NMR chemical shifts. 2-fluorohistidine and 4-fluorohistidine, studied here with DFT methods, have even more capabilities for biophysical studies, as their altered pKa values, relative to histidine, allow for studies of the role of proton transfer and tautomeric state in enzymatic mechanisms. Considering the two tautomeric forms of histidine, it was found that 2-fluorohistidine primarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…We recently reported similar calculated effects for 4-fluorohistidine (increased shielding with dielectric constant), although calculated shielding of 2-fluorohistidine decreases with higher dielectric. 51 The only method with notable deviations between shielding and dielectric is M062X; however, the method did not perform better at ordering the relative shielding/deshielding in the presence of different solvents. Overall, our results indicate that electronic structure calculations with implicit solvent models are not able to reliably predict solvent effects on fluorine chemical shifts.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We recently reported similar calculated effects for 4-fluorohistidine (increased shielding with dielectric constant), although calculated shielding of 2-fluorohistidine decreases with higher dielectric. 51 The only method with notable deviations between shielding and dielectric is M062X; however, the method did not perform better at ordering the relative shielding/deshielding in the presence of different solvents. Overall, our results indicate that electronic structure calculations with implicit solvent models are not able to reliably predict solvent effects on fluorine chemical shifts.…”
Section: Resultsmentioning
confidence: 96%
“…For histidine, the different tautomeric states (τ and π) of 2-fluoro and 4-fluoro histidines and analogues were considered. 195051 The fluorine chemical shift of the lowest energy tautomer is reported. In the two amino acids studied with trifluoromethyl groups, the fluorine chemical shifts are reported as the average of the three fluorine chemical shifts.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous analysis of electronic structure calculations of histidine suggested, from bond polarity, that the C4(Cδ)–H bond of histidine is a viable hydrogen bond donor. 9,12–14 Investigation of neutron diffraction structures, allowing for identification of tautomeric/protonation state, yielded experimental evidence for Cδ–H hydrogen bonds in proteins, in addition to C2(Cε)–H hydrogen bonds, which have been identified previously as a type of hydrogen bond. Common motifs for histidine Cδ–H hydrogen bonds in crystal structures include coordinated water molecules and interactions in beta sheets and loops that presumably help stitch together the secondary structure.…”
Section: Discussionmentioning
confidence: 96%
“…It should be noted that data from Nanda and Schmiedekamp revealed that all N–H⋯O interactions involving nitrogen of histidine (and histidinium) showed a propensity for the H-bond to dictate the geometry of the atoms involved in the hydrogen bond. 11 In our previous studies of fluorohistidine, 9,12–14 evaluation of charges calculated by electrostatic potential indicated that the τ-tautomer and protonated (histidinium) forms of histidine have a quite polar Cδ–H bond, which prompted this investigation.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation